2008
DOI: 10.1152/ajpregu.00144.2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sedentary versus physically active conditions on regulation of plasma renin activity and vasopressin

Abstract: Mueller PJ. Influence of sedentary versus physically active conditions on regulation of plasma renin activity and vasopressin. Am J Physiol Regul Integr Comp Physiol 295: R727-R732, 2008. First published May 28, 2008 doi:10.1152/ajpregu.00144.2008.-Physical inactivity is an independent risk factor for cardiovascular disease. Sedentary animals compared to physically active controls exhibit enhanced sympathoexcitatory responses, including arterial baroreflexmediated sympathoexcitation. Hypotension-induced symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Similarly, both parvocellular and magnocellular subnuclei of the PVN displayed increases FLI following HEM compared to CONs that was similar in both the SED and EX animals. Since both these regions contain vasopressinergic neurons that project to the posterior pituitary (magnocellular region) or within the CNS (parvocellular region) (Swanson and Sawchenko 1983; Badoer 2001) these data support previous work demonstrating that 6–8 weeks of daily EX may not impact vasopressin release in response to hypotension (Mueller 2008). Alternatively, there is evidence that EX training can enhance the excitability of centrally projecting PVN neurons (Jackson 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, both parvocellular and magnocellular subnuclei of the PVN displayed increases FLI following HEM compared to CONs that was similar in both the SED and EX animals. Since both these regions contain vasopressinergic neurons that project to the posterior pituitary (magnocellular region) or within the CNS (parvocellular region) (Swanson and Sawchenko 1983; Badoer 2001) these data support previous work demonstrating that 6–8 weeks of daily EX may not impact vasopressin release in response to hypotension (Mueller 2008). Alternatively, there is evidence that EX training can enhance the excitability of centrally projecting PVN neurons (Jackson 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Based on previous studies showing that exercise training can either slightly enhance [(Brum, Da Silva et al 2000; Sakuragi 2006; Harthmann 2007)], attenuate (Chen 1996), or not change (Liu 2002) baroreflex sensitivity to hypotension, we hypothesized that chronic exercise would only modestly alter the compensatory response of hemorrhage. Alternatively, it was hypothesized that daily exercise would significantly alter the decompensatory phase of severe HEM based on recent work demonstrating that cardiac afferent activity (Di Carlo 1990), hormonal responses to hypotension (Mueller 2008) and stress (Sasse 2008) are all altered by daily exercise, in addition to central changes involving sympathoexcitatory (Zheng 2005; Mueller 2007) and sympathoinhibitory (De Souza 2001; Mueller and Hasser 2006) circuits in the brain. Accordingly, we also hypothesized that voluntary exercise training would alter the pattern of cellular activation (as marked by c-Fos immunoreactivity) in rostral brainstem regions identified to be involved in autonomic control during HEM including the locus coeruleus (LC; compensation), ventrolateral periaqueductal gray (vlPAG; decompensation) and the lateral parabrachial nucleus (LPBN, recovery).…”
Section: Introductionmentioning
confidence: 99%
“…ADH is released from the posterior pituitary in response to low blood volume and is regulated independently of the baroreflex (Goetz et al 1984; Mueller 2008; Quail et al 1987). ADH can increase 5 fold and account for 70% of blood pressure recovery after hemorrhage (Cowley et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies are highly clinically relevant and suggest reversal of changes associated with disease states, there is also increasing evidence that in the absence of overt disease, physical activity or inactivity alone can produce central alterations that influence sympathetic nervous system regulation (74,80,81). Our recent study comparing spontaneous wheel running to "normal" cage activity emphasized this point and suggested that a sedentary lifestyle alone or in combination with other cardiovascular risk factors may contribute to cardiovascular disease via influences on central structures involved in regulation of the sympathetic nervous system (75). We have focused our efforts on the RVLM as a key brain region involved in the generation of sympathetic outflow.…”
Section: Physical (In)activity-dependent Neuroplasticity In Sympathetmentioning
confidence: 98%
“…In addition, examination of a variety of factors, including the type of exercise (aerobic vs. resistance), duration, intensity, environmental conditions, and individual responsiveness to exercise or inactivity are important, clinically relevant issues. Like other laboratories (39,40,60), we continue to promote the development of experimental designs and models that examine this fundamental question by treating the sedentary condition as a contributing factor to chronic disease and physically active conditions as the "normal" healthy control (15,75). We feel that this reflects more than a semantic difference but rather reflects an important and distinct paradigm shift as to what should be considered a "normal" or "control" group.…”
Section: Perspectives and Significancementioning
confidence: 99%